PENGARUH TINGKAT PENDIDIKAN, PENDAPATAN DAN KONSUMSI TERHADAP JUMLAH PENDUDUK MISKIN DI PROVINSI JAWA TIMUR - Maulidah, Fadlliyah; Soejoto, Ady (UNIVERSITAS NEGERI SURABAYA, 2015)
This research aims to analyze the influence of education level, income and consumption on the number of poor people in the east java province partially and simultaneously. The population of this research is poor people in east java province from the year 2009-2013. The technique of sampling applies purposive sampling. Furthermore, the method of data collection uses method of documentation while the method of data analysis is regression analysis techniques of panel data. The result of data analysis shows that in partial the education level does not influence significantly to the number of poor people of east java. However, the income and consumption influence significantly to the number of poor people of east java. Moreover, simultaneously the education level, income and consumption influence significantly to the number of poor people of east java